1983
DOI: 10.1128/aem.45.3.843-849.1983
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of glucose and cellobiose by cellulolytic mesophilic Clostridium sp. strain H10

Abstract: The metabolism of strain H10, a cellulolytic mesophilic Clostridium sp., was studied on glucose and cellobiose as energy and carbon sources. The main products of fermentation of both sugars were acetate, lactate, and ethanol. At low sugar levels, molar growth yields were better for cellobiose than for glucose. In both cases, an inhibition of growth was observed between 1 and 2 g/liter and a total inhibition after the latter concentration. Inhibition was not the result of low pH due to acid formation; growth un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 19 publications
(25 reference statements)
3
52
0
Order By: Relevance
“…Whereas the effects of acidic conditions on the growth of cellulolytic rumen bacteria have been the subject of considerable research [133][134][135][136][137], few investigations have been devoted to cellulolytic clostridia. Contrary to the assumption that the buffering capacity of the culture medium is sufficient to compensate the acidification [97,99], reinvestigation of cellulose degradation by C. cellulolyticum demonstrated that the growth inhibition observed with batch cultures, performed in penicillin flasks, is essentially the result of a low pH due to acid production in the course of fermentation. Cellulose-limited chemostats confirmed the dramatic effect of environmental acidification which influences chiefly biomass formation rather than cellulose degradation and assimilation [98].…”
Section: The Metabolisation Of Carbon In C Cellulolyticummentioning
confidence: 89%
See 1 more Smart Citation
“…Whereas the effects of acidic conditions on the growth of cellulolytic rumen bacteria have been the subject of considerable research [133][134][135][136][137], few investigations have been devoted to cellulolytic clostridia. Contrary to the assumption that the buffering capacity of the culture medium is sufficient to compensate the acidification [97,99], reinvestigation of cellulose degradation by C. cellulolyticum demonstrated that the growth inhibition observed with batch cultures, performed in penicillin flasks, is essentially the result of a low pH due to acid production in the course of fermentation. Cellulose-limited chemostats confirmed the dramatic effect of environmental acidification which influences chiefly biomass formation rather than cellulose degradation and assimilation [98].…”
Section: The Metabolisation Of Carbon In C Cellulolyticummentioning
confidence: 89%
“…The accumulation of G1P leads to the rerouting of metabolism through, first, the production of glycogen and, second, the exopolysaccharide biosynthesis. In C. cellulolyticum, the presence of uncharacterised exopolysaccharides was suggested early [97]. The synthesis of glycogen was also reported but contrary to ruminal cellulolytic bacteria where it can represent between 30% and 60% of the dry weight [153], in C. cellulolyticum its accumulation is limited to between 3% and 5% [150].…”
Section: The Glucose 1-phosphate/glucose 6-phosphate Metabolic Nodementioning
confidence: 99%
“…The main products of cellobiose fermentation by C. cellulolyticum were acetate, ethanol, lactate, H 2 , and CO 2 (Giallo et al, 1983); because of the very low concentrations of extracellular pyruvate detected in the medium, we have omitted this compound in the reactions leading to the formation of the metabolites. Strobel et al (1995) demonstrated in C. thermocellum that the transport of cellodextrin, cellobiose, or glucose was ATP-dependent and that intracellular cellobiose was converted to glucose 1-phosphate and glucose by cellobiose phosphorylase (EC 2.4.1.20) (Giallo, 1984).…”
Section: Calculationsmentioning
confidence: 99%
“…In most natural environments, mesophilic cellulolytic clostridia play a major role in cellulose decomposition Leschine, 1995), and it became apparent that their biotechnological exploitation necessitates knowledge about biomass formation and metabolic features which control the rates, yields, and kinds of fermentation products. Clostridium cellulolyticum, a mesophilic bacterium able to degrade crystalline cellulose (Petitdemange et al, 1984) has been studied with regard to its ability to use various substrates (Giallo et al, 1983(Giallo et al, , 1985Gelhaye et al, 1993a,b;Payot et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation